Carbohydrate metabolism and cell protection mechanisms differentiate drought tolerance and sensitivity in advanced potato clones (Solanum tuberosum L.) - Legay, S.; Lefevre, I.; Lamoureux, D.; Barreda, C.; Tincopa, L.R.; Gutiérrez, R.; Quiróz, R.; Hoffman, L.; Hausman, J.F.; Bonierbale, Merideth W.; Evers, D.; Schafleitner, R. (Springer, 2011)
In potatoes and many other crops, drought is one of the most important environmental constraints leading to yield loss. Development of drought-tolerant cultivars is therefore required for maintaining yields under climate change conditions and for the extension of agriculture to sub-optimal cropping areas. Drought tolerance mechanisms have been well described for many crop plants including Native Andean potato. However, knowledge on tolerance traits suitable for commercial potato varieties is scarce. In order to describe drought tolerance mechanisms that sustain potato yield under water stress, we have designed a growth-chamber experiment with two Solanum tuberosum L. cultivars, the more drought tolerant accession 397077.16, and the sensitive variety Canchan. After 21 days of drought exposure, gene expression was studied in leaves using cDNA microarrays. The results showed that the tolerant clone presented more differentially expressed genes than the sensitive one, suggesting greater stress response and adaptation. Moreover, it exhibited a large pool of upregulated genes belonging to cell rescue and detoxication such as LEAs, dehydrins, HSPs, and metallothioneins. Transcription factors related to abiotic stresses and genes belonging to raffinose family oligosaccharide synthesis, involved in desiccation tolerance, were upregulated to a greater extent in the tolerant clone. This latter result was corroborated by biochemical analyses performed at 32 and 49 days after drought that showed an increase in galactinol and raffinose especially in clone 397077.16. The results depict key components for the drought tolerance of this advanced potato clone.